BUILDING A MECHANISM TO INCREASE THE LEVEL OF FINANCIAL AND ECONOMIC SECURITY OF HIGHER EDUCATION INSTITUTIONS - NYZHNYK, Viktor; NYZHNYK, Iryna; LYSAK, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ukraine’s entry into the community of highly developed countries requires constant monitoring of the state of the educational and scientific environment, assessment of the level of financial and economic security of higher education institutions, development of measures to improve this level. However, without building a structural model of the mechanism for improving the level of financial and economic security, higher education institutions will not be able to identify threats to their activities, assess the actual state of financial and economic security by deviations from the normative state and eliminate negative deviations for more sustainable development. Based on the considered scientific approaches to financial and economic security of higher education institutions, a structural model of the mechanism of improving financial and economic security of higher education institutions is built, which includes: goals, objectives, principles, methods, levers, operating blocks and organizational support of the mechanism. The procedure for calculating the integrated indicator of the level of financial and economic security of higher education institutions, which is part of the organizational support of the mechanism, and a list of measures to improve the level of financial and economic security of higher education institutions, which are part of the mechanism. The authors propose a scientific approach, which involves determining the overall level of financial and economic security of higher education based on the calculation of aggregate indicators of each component and their weights, which will then offer a list of measures to bring the actual level to its normative level. The development of measures to increase the level of financial and economic security is related to the need to consider new factors facing domestic higher education institutions, and socio-economic and institutional challenges, challenges facing Ukraine in the development of European integration processes and new conditions in global environment.